Resistance paste and thick film type resistor
Through the combination of specific glass phases and metal oxides, the corrosion resistance and bonding strength of the resistive paste are improved, and the problem of poor stability of the resistor film layer in harsh environments is solved, and the long-term resistance under high voltage and strong external force is realized. Work stably.
Patent Information
- Application Number
- CN202411424209.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-07
AI Technical Summary
The corrosion resistance and bonding strength of the resistive film layer made of existing resistive slurries are poor, and cannot work stably in harsh environments for a long time, affecting the performance and service life of the resistor.
Using three glass phases (glass phases A, B, C) with specific component content, control the mass percentage relationship, combine metal oxides and conductive phases, and prepare resistive film layers through screen printing technology and sintering to improve Corrosion resistance and bonding strength.
It realizes excellent corrosion resistance and bonding strength of the resistive film layer, and has the stability of the resistance value, and can work for a long time under high voltage and strong external forces. The resistance value change rate is less than 1%, which is suitable for harsh environments.
Smart Images

Figure BDA0005081696110000071 
Figure BDA0005081696110000082 
Figure BDA0005081696110000083
Abstract
Description
Technical Field
[0001] The invention belongs to the field of resistor paste, and in particular relates to a resistor paste and a thick film chip resistor. Background Art
[0002] Thick film chip resistors are important electronic components and are widely used in thick film circuits, hybrid integrated circuits, and electronic devices. The resistance characteristics of thick film chip resistors mainly depend on the resistor film layer, which is formed by printing thick film resistor paste on an insulating substrate and sintering it. In some special application scenarios, the operating environment of the resistor is relatively harsh. It needs to work for a long time under high voltage and strong external force, and the resistance value of the resistor film must remain stable. Therefore, the resistor film layer in this type of resistor should have excellent corrosion resistance and a high bonding strength between the substrate and the film layer to avoid the phenomenon of corrosion through the resistor film layer or the film layer falling off the substrate, resulting in large changes in resistance value, affecting the performance and service life of the resistor device. However, the resistor film layer made of conventional resistor paste has poor corrosion resistance and bonding strength, and cannot be used in harsh environments. It is necessary to improve the resistor paste formula to improve related performance, thereby expanding the application field of thick film resistor paste. Summary of the invention
[0003] In view of the problems of poor corrosion resistance and bonding strength of the resistor film layer made of the resistor paste involved in the above-mentioned prior art, the present invention will provide a resistor paste and a thick film chip resistor.
[0004] To achieve the above purpose, the following technical solutions are specifically included:
[0005] A resistor paste includes a glass phase with a mass percentage of 1-35%, wherein the glass phase includes a glass phase A, a glass phase B and a glass phase C, and satisfies the following relationship: a=ω A / (ω B +ω C ), 0.3≤a≤3, where ω A is the mass percentage of the glass phase A in the resistor paste, ω B is the mass percentage of the glass phase B in the resistor paste, ω C is the mass percentage of the glass phase C in the resistor paste;
[0006] Taking the total mass percentage of the glass phase A as 100%, the glass phase A includes the following components in mass percentage: SiO2 32-51%, Al2O3 11-25%, B2O3 12-23%, metal oxide M5-35%, wherein the metal oxide M is selected from at least two of CaO, MgO, SrO, and BaO;
[0007] Taking the total mass percentage of the glass phase B as 100%, the glass phase B includes the following components in mass percentage: SiO2 30-50%, Al2O3 0-5%, B2O3 5-20%, ZnO 10-20%, metal oxide N 5-25%, metal oxide R 5-25%, wherein the metal oxide N is selected from at least two of SnO2, TeO2, TiO2, and ZrO2;
[0008] Taking the total mass percentage of the glass phase C as 100%, the glass phase C includes the following components in mass percentage: SiO2 15-30%, Al2O3 0-15%, B2O3 0-25%, metal oxide P 30-55%, metal oxide R 0-20%, wherein the metal oxide P is selected from at least one of CuO, NiO and ZnO;
[0009] In the glass phase B and the glass phase C, the metal oxide R is each selected from at least one of Li2O, Na2O, and K2O.
[0010] The present invention selects three glass phases with specific component contents to control the contents of the three glass phases. When 0.3≤a≤3, the resistor film layer obtained after sintering the resistor paste can have excellent corrosion resistance and bonding strength; conversely, if a<0.3, the corrosion resistance of the resistor film layer cannot meet the application requirements, and if a>3, the bonding strength of the resistor film layer cannot meet the requirements.
[0011] In the resistor paste of the present invention, due to the presence of metal oxide M in the glass phase A, the oxidation of the conductive phase with strong reducibility (such as conductive materials such as copper, nickel, copper-nickel and gold) can be inhibited, thereby improving the corrosion resistance of the film layer after the resistor paste is sintered. ZnO in the glass phase B can improve the stability of the resistor film layer on the one hand, and on the other hand, ZnO can form a solid solution with the substrate interface as a crystallization phase to improve the bonding strength of the resistor film layer; at the same time, the presence of metal oxide N can promote crystallization, thereby effectively enhancing the bonding strength of the resistor film layer. Glass phase C can adjust the softening point of the glass phase to avoid the addition of ZnO causing the glass phase softening point temperature to be too high, resulting in poor wetting of the substrate during the sintering of the resistor paste, which ultimately reduces the bonding strength of the resistor film layer.
[0012] Preferably, based on the total mass percentage of the glass phase being 100%, the mass percentage of the glass phase A is 30-65%, the mass percentage of the glass phase B is 15-40%; and the mass percentage of the glass phase C is 15-40%.
[0013] In the glass phase A, in addition to the necessary SiO2, Al2O3, B2O3 and metal oxide M, other oxides such as TiO2 and Na2O may also be included, without any particular limitation.
[0014] In the glass phase B, in addition to the necessary SiO2, Al2O3, B2O3, ZnO, metal oxide N and metal oxide R, other oxides such as CuO and Ta2O5 may also be included, without any special restrictions.
[0015] The glass phase C may include, in addition to the necessary SiO2, Al2O3, B2O3, metal oxide P and metal oxide R, other oxides such as MnO2 and Ta2O5, without any particular limitation.
[0016] Preferably, in the glass phase A, the following relationship is satisfied: b=(ω SiO2 +ω Al2O3 +ω B2O3 ) / ω M , 3≤b≤10, where ω SiO2 is the mass percentage of SiO2 in the glass phase A, ω Al2O3 is the mass percentage of Al2O3 in the glass phase A, ω B2O3 is the mass percentage of B2O3 in the glass phase A, ω M is the mass percentage of the metal oxide M in the glass phase A.
[0017] When the b value is within the above range, the corrosion resistance and bonding strength of the resistor film layer are better; if b<3, the content of SiO2, Al2O3 and B2O3 forming the glass phase network skeleton decreases, affecting the stability of the resistor film layer and reducing the bonding strength; if b>10, the content of metal oxide M decreases, resulting in a decrease in the corrosion resistance of the resistor film layer.
[0018] Preferably, in the glass phase B, the following relationship is satisfied: c = (ω SiO2 +ω Al2O3 +ω B2O3 +ω ZnO ) / (ω N +ω BR ), 1.4≤c≤6.8, where ω SiO2 is the mass percentage of SiO2 in the glass phase B, ω Al2O3 is the mass percentage of Al2O3 in the glass phase B, ω B2O3 is the mass percentage of B2O3 in the glass phase B, ω ZnO is the mass percentage of ZnO in the glass phase B, ω Nis the mass percentage of the metal oxide N in the glass phase B, ω BR is the mass percentage of the metal oxide R in the glass phase B.
[0019] When the c value is within the above range, the bonding strength and stability of the resistor film layer are better; if c < 1.4, the bonding strength of the resistor film layer decreases due to the relatively lower ZnO content; if c > 6.8, the bonding strength of the resistor film layer will also decrease due to the lower content of metal oxide N that promotes crystallization and the metal oxide R that lowers the glass softening point temperature, and the difference between the metal oxide N and the ZnO content increases.
[0020] Preferably, in the glass phase C, the following relationship is satisfied: d = (ω SiO2 +ω Al2O3 +ω B2O3 ) / (ω P +ω CR ), 0.68≤d≤1.85, where ω SiO2 is the mass percentage of SiO2 in the glass phase C, ω Al2O3 is the mass percentage of Al2O3 in the glass phase C, ω B2O3 is the mass percentage of B2O3 in the glass phase C, ω P is the mass percentage of the metal oxide P in the glass phase C, ω CR is the mass percentage of the metal oxide R in the glass phase C.
[0021] When the d value is within the above range, the bonding strength of the resistor film layer is further improved. If d < 0.68, the softening point of the glass phase is too low, the appearance quality of the film layer after the resistor paste is sintered is poor, and the resistance discreteness of the resistor film layer is reduced; if d > 1.85, the effect of reducing the softening point of the glass phase is reduced, so that the wettability of the resistor paste to the substrate is reduced, and the bonding strength of the resistor film layer is reduced.
[0022] Preferably, the average particle size of the glass phase is 0.5-5 μm.
[0023] Preferably, the composition further comprises the following components in percentage by mass: 40-85% conductive phase, 2-10% resin, 5-20% organic solvent, 0-10% inorganic filler, and 0-10% organic additive.
[0024] Preferably, the conductive phase includes copper powder and nickel powder, and satisfies the following relationship: s=ω Cu / ω Ni , 0.6≤s≤11, where ω Cu is the mass percentage of the copper powder in the resistor paste, ω Niis the mass percentage of the nickel powder in the resistor paste.
[0025] Further preferably, the conductive phase includes copper powder and nickel powder, and satisfies the following relationship: s=ω Cu / ω Ni , 0.67≤s≤10. By controlling the content of copper powder and nickel powder, the resistor film layer can have excellent TCR performance and resistance range. If s<0.67, the resistance of the resistor film layer cannot be effectively reduced and the resistance range is reduced; if s>10, the TCR performance of the resistor film layer deteriorates.
[0026] Preferably, the average particle size of the conductive phase is 0.1-5 μm.
[0027] More preferably, the average particle size of the copper powder is 0.2-5 μm, and the average particle size of the nickel powder is 0.1-2 μm.
[0028] Preferably, the resin is selected from at least one of ethyl cellulose, epoxy resin, polyurethane resin, polyester resin, acrylic resin, alkyd resin, phenolic resin, petroleum resin, terpene resin, modified rosin, polyethylene, polypropylene, and polyamide.
[0029] Preferably, the organic solvent is selected from at least one of diethylene glycol butyl ether, diethylene glycol butyl ether acetate, terpineol, turpentine, isobornyl acetate, benzyl acetate, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, dibutyl phthalate, toluene, xylene, butanone, cyclohexanone, propylene glycol monomethyl ether, dimethyl phthalate, petroleum ether, and mineral oil.
[0030] Preferably, the inorganic filler is selected from at least one of aluminum oxide, zirconium oxide, manganese oxide, titanium oxide, silicon oxide and nickel oxide.
[0031] Preferably, the organic additive is selected from at least one of polyethylene wax, polypropylene wax, polyamide wax, hydrogenated castor oil, organic bentonite, fatty acids, aliphatic amides, aliphatic esters, phosphate esters, polyamides, and polyacrylates.
[0032] More preferably, the fatty acids include at least one of oleic acid and stearic acid.
[0033] More preferably, the aliphatic amides include vinyl bisstearamide.
[0034] More preferably, the fatty ester is at least one of stearic acid monoglyceride and tristearic acid glyceride.
[0035] A method for preparing the resistor paste comprises the following steps: mixing various raw materials evenly to obtain the resistor paste.
[0036] Preferably, the process of uniformly mixing the raw materials includes the following steps:
[0037] (1) uniformly dissolving the resin and the organic additive in an organic solvent under heating, filtering and cooling to obtain an organic carrier;
[0038] (2) Adding the conductive phase, the glass phase and the inorganic filler into the organic carrier, stirring and premixing them, and then rolling them to obtain the resistor paste.
[0039] A resistor film layer is prepared by sintering the resistor paste.
[0040] A method for preparing a resistor film layer comprises the following steps: printing the resistor paste on an alumina substrate with a copper electrode by screen printing, and sintering at 850-1000° C. in a nitrogen atmosphere to obtain a resistor film layer.
[0041] A thick film chip resistor comprises a resistor film layer prepared by sintering the resistor paste.
[0042] The thick film chip resistor of the present invention is circulated under the conditions of temperature 85°C±2°C and humidity 85%±2%RH, with power on for 1.5 hours and power off for 0.5 hours at the rated voltage or the maximum operating voltage, and the cycle is continued for 1000 hours. The resistance change rate |△R| of the resistor film layer in the thick film chip resistor is ≤1%.
[0043] The thick film chip resistor of the present invention is welded to a PCB board, and a vertical pressure is applied to the PCB board with a vertical downward pressure distance of 2 mm, so that the PCB board is bent, and the resistance value change rate |△R| of the resistor film layer in the thick film chip resistor is ≤1%.
[0044] The thick film chip resistor of the present invention has a dispersion coefficient RSD≤5% among n thick film chip resistors, and n≥10.
[0045] The thick film chip resistor of the present invention calculates TCR at -55-125°C based on 25°C. When the resistance R of the thick film chip resistor is ≤0.1Ω, 500ppm / °C<|TCR|≤1000ppm / °C. When the resistance R of the thick film chip resistor is >0.1Ω, 100ppm / °C<|TCR|≤200ppm / °C.
[0046] Compared with the prior art, the present invention has the following beneficial effects: by selecting three glass phases with specific component contents and controlling the contents of the three glass phases, the present invention can make the resistor film layer obtained after sintering the resistor paste have excellent corrosion resistance and bonding strength. DETAILED DESCRIPTION
[0047] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.
[0048] In the present invention, a=ω A / (ω B +ω C ), 0.3≤a≤3, where ω A is the mass percentage of the glass phase A in the resistor paste, ω B is the mass percentage of the glass phase B in the resistor paste, ω C is the mass percentage of the glass phase C in the resistor paste.
[0049] In some embodiments, the glass phase A satisfies the following relationship: b = (ω SiO2 +ω Al2O3 +ω B2O3 ) / ω M , 3≤b≤10, where ω SiO2 is the mass percentage of SiO2 in the glass phase A, ω Al2O3 is the mass percentage of Al2O3 in the glass phase A, ω B2O3 is the mass percentage of B2O3 in the glass phase A, ω M is the mass percentage of the metal oxide M in the glass phase A.
[0050] In some embodiments, the glass phase B satisfies the following relationship: c = (ω SiO2 +ω Al2O3 +ω B2O3 +ω ZnO ) / (ω N +ω BR ), 1.4≤c≤6.8, where ω SiO2 is the mass percentage of SiO2 in the glass phase B, ω Al2O3 is the mass percentage of Al2O3 in the glass phase B, ω B2O3 is the mass percentage of B2O3 in the glass phase B, ω ZnO is the mass percentage of ZnO in the glass phase B, ω N is the mass percentage of the metal oxide N in the glass phase B, ω BR is the mass percentage of the metal oxide R in the glass phase B.
[0051] In some embodiments, the glass phase C satisfies the following relationship: d = (ω SiO2 +ω Al2O3 +ω B2O3 ) / (ω P +ω CR ), 0.68≤d≤1.85, where ω SiO2 is the mass percentage of SiO2 in the glass phase C, ω Al2O3 is the mass percentage of Al2O3 in the glass phase C, ω B2O3 is the mass percentage of B2O3 in the glass phase C, ω P is the mass percentage of the metal oxide P in the glass phase C, ω CR is the mass percentage of the metal oxide R in the glass phase C.
[0052] In some embodiments, the conductive phase includes copper powder and nickel powder, and satisfies the following relationship: s=ω Cu / ω Ni , 0.6≤s≤11, more preferably, 0.67≤s≤10, where ω Cu is the mass percentage of the copper powder in the resistor paste, ω Ni is the mass percentage of the nickel powder in the resistor paste.
[0053] In the following examples and comparative examples, the average particle size of the copper powder is 2 μm; the average particle size of the nickel powder is 0.35 μm, and the average particle sizes of the glass phase A, glass phase B, and glass phase C are all 3.5 μm.
[0054] In the following embodiments and comparative examples, glass phase A includes 6 types, namely glass phases A1, A2, A3, A4, A5 and A6; glass phase B includes 6 types, namely glass phases B1, B2, B3, B4, B5 and B6; glass phase C includes 6 types, namely glass phases C1, C2, C3, C4, C5 and C6. The specific compositions of glass phase A, glass phase B and glass phase C are shown in Tables 1-3.
[0055] Example 1
[0056] (1) preparing glass phase A1, glass phase B1, and glass phase C1 respectively according to the component ratios in Tables 1-3;
[0057] (2) Weighing raw materials according to the component formula in Table 4-5, 3.5wt% of resin and 0.5wt% of organic additives were uniformly dissolved in 8wt% of organic solvent under heating and stirring, and then filtered and cooled to obtain a viscous colloidal organic carrier;
[0058] (3) Weigh the raw materials according to the component formula in Table 4-5, add 80wt% conductive phase (70wt% Cu and 10wt% Ni), 7wt% glass phase, and 1wt% inorganic filler into the organic carrier, stir and premix, and then fully disperse them through a three-roll mill to finally obtain a thick film resistor slurry.
[0059] Embodiment 2-5
[0060] The difference between Example 2-5 and Example 1 is that the a value is changed by changing the content ratio of glass phase A1, glass phase B1 and glass phase C1. For details, see Table 4-5.
[0061] Examples 6-12
[0062] Compared with Example 1, the only difference between Examples 6-12 is that the types of the three glass phases are different, resulting in different b, c, and d values. See Table 4-5 for details.
[0063] Examples 13-18
[0064] The only difference between Examples 13-18 and Example 1 is that the s value is changed by changing the content of copper powder and nickel powder, as shown in Table 5 for details.
[0065] Examples 19-27
[0066] Compared with Example 1, the types and contents of the conductive phase, glass phase, resin, organic solvent, inorganic filler and inorganic additive in Examples 19-27 are different, see Table 4-5 for details.
[0067] Comparative Example 1-2
[0068] The difference between Comparative Example 1-2 and Example 1 is that the a value is changed by changing the content ratio of glass phase A1, glass phase B1 and glass phase C1. For details, see Table 4-5.
[0069] Table 1 Glass phase A (100 wt%)
[0070]
[0071]
[0072] Table 2 Glass phase B (100 wt%)
[0073]
[0074] Table 3 Glass phase C (100 wt%)
[0075]
[0076] Table 4
[0077]
[0078]
[0079]
[0080] Table 5 (resistance paste 100wt%)
[0081]
[0082]
[0083]
[0084] Performance Testing:
[0085] (1) The component types and contents of the conductive phase and glass phase of copper powder and nickel powder can be obtained by XRF (X-ray fluorescence spectrometer) detection.
[0086] (2) The particle size of copper powder, nickel powder and glass phase can be obtained by SEM, EDS and laser particle size analyzer.
[0087] (3) Corrosion resistance
[0088] The resistor pastes of the above-mentioned embodiments and comparative examples were respectively printed on an alumina substrate with a copper electrode by screen printing, and sintered at 900°C in a nitrogen atmosphere to obtain a resistor layer size sample with 1206 chip resistor specifications. The sample was placed under the conditions of temperature 85°C±2°C and humidity 85%±2%RH, and energized for 1.5 hours at the rated voltage or the maximum working voltage, and powered off for 0.5 hours for a cycle, and the cycle was repeated for 1000 hours. Then, the resistance value change rate |△R| was calculated by testing the resistance value of the resistor layer before and after the experiment. Requirement: The product is qualified when |△R|≤1%.
[0089] (4) Bonding strength
[0090] The resistor pastes of the above-mentioned embodiments and comparative examples were respectively printed on an alumina substrate with a copper electrode by screen printing, and sintered at 900°C in a nitrogen atmosphere to obtain a resistor layer size sample with a specification of 1206 chip resistor. The test sample was welded on a PCB board, and a vertical pressure was applied to the PCB board with a vertical downward pressure distance of 2mm, so that the PCB board was deformed and the test sample was bent, and then the resistance change rate |△R'| was calculated by testing the resistance value of the resistor layer before and after the experiment. Requirement: |△R'|≤1%.
[0091] If the resistance layer has poor bonding strength with the substrate, the resistance layer will easily peel off from the substrate and break when the test sample is bent, resulting in a high resistance change rate; if the resistance layer has good bonding strength with the substrate, the resistance layer will deform together with the alumina substrate when the test sample is bent, and no peeling will occur, resulting in a low resistance change rate. Therefore, the resistance change rate |△R'| obtained from the above test can determine the bonding strength between the resistance layer and the substrate.
[0092] (5) Resistance value Size and dispersion coefficient RSD
[0093] The resistor pastes of the above-mentioned embodiments and comparative examples were respectively printed on an alumina substrate with a copper electrode by screen printing, and sintered at 900°C in a nitrogen atmosphere to obtain resistor layer size samples of 1206 chip resistor specifications. The number of test samples in each embodiment or comparative example is n; the resistance value R of each sample is tested using a resistance measuring machine. i , calculate the average resistance value of n test samples The resistance dispersion coefficient is calculated by the formula When RSD≤5%, it is a qualified product. In this embodiment and comparative example, n is 500.
[0094] (6) TCR test
[0095] The resistor pastes of the above-mentioned embodiment and comparative example were respectively printed on an alumina substrate with a copper electrode by screen printing, and sintered at 900°C in a nitrogen atmosphere to obtain a resistor layer size sample of 1206 chip resistor specification. H(C)TCR was calculated according to the following formula:
[0096] Generally, 25℃ is used as the benchmark, and the resistance value tested at 25℃ is R 25 , the resistance value tested at 125℃ for 10min is R 125 , the resistance value tested at -55℃ for 10min is R -55 , HTCR and CTCR are denoted as H(C)TCR;
[0097] Determination method:
[0098] When R 25 When ≤0.1Ω:
[0099] a: 0ppm / ℃≤|H(C)TCR|≤500ppm / ℃ is excellent;
[0100] b: 500ppm / ℃<|H(C)TCR|≤1000ppm / ℃ is qualified;
[0101] c: |H(C)TCR|>1000ppm / ℃ is unqualified.
[0102] When R 25 >0.1Ω:
[0103] a: 0ppm / ℃≤|H(C)TCR|≤100ppm / ℃ is excellent;
[0104] b: 100ppm / ℃<|H(C)TCR|≤200ppm / ℃ is qualified; c: |H(C)TCR|>200ppm / ℃ is unqualified.
[0105] The performance test results are shown in Table 6.
[0106] Table 6
[0107]
[0108]
[0109] It can be seen from Examples 1-5 and Comparative Examples 1-2 that when 0.3≤a≤3, the resistor film layer obtained after sintering the resistor paste can have excellent corrosion resistance and bonding strength; conversely, if a<0.3, the corrosion resistance of the resistor film layer cannot meet the application requirements, and if a>3, the bonding strength of the resistor film layer cannot meet the requirements.
[0110] It can be seen from Examples 1 and 6-12 that when 3≤b≤10, the corrosion resistance and bonding strength of the resistor film layer are better; in Example 6, b<3, the content of SiO2, Al2O3 and B2O3 forming the glass network skeleton decreases, affecting the stability of the resistor film layer and reducing the bonding strength; in Example 8, b>10, the content of metal oxide M decreases, resulting in a decrease in the corrosion resistance of the resistor film layer. When 1.4≤c≤6.8, the bonding strength and stability of the resistor film layer are better; in Example 9, c<1.4, the bonding strength of the resistor film layer decreases due to the relatively reduced ZnO content; in Example 10, c>6.8, the bonding strength of the resistor film layer is also reduced due to the reduced content of metal oxide N that promotes crystallization and metal oxide R that reduces the glass softening point temperature, and the difference between it and the ZnO content increases. When 0.68≤d≤1.85, the bonding strength of the resistor film layer is further improved. In Example 12, d is less than 0.68, the softening point of the glass phase is too low, the appearance quality of the film layer after sintering the resistor paste is poor, the RSD of the resistor film layer increases, and the discreteness of the resistance value increases; in Example 11, d is greater than 1.85, the effect of lowering the softening point of the glass phase is reduced, the wettability of the resistor paste to the substrate is reduced, and the bonding strength of the resistor film layer is reduced.
[0111] It can be seen from Examples 1, 13-18, and 28-33 that the value range of s can be 0.6≤s≤11. When 0.67≤s≤10, the resistor film layer can have excellent TCR performance and resistance range; in Example 28, s<0.67, the resistance of the resistor film layer cannot be effectively reduced, and the resistance range is narrowed; in Example 33, s>10, the TCR performance of the resistor film layer deteriorates.
[0112] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A resistor paste, characterized in that: The glass phase includes 1-35% by mass, wherein the glass phase includes glass phase A, glass phase B and glass phase C, and satisfies the following relationship: a=ω A / (ω B +ω C ), 0.3≤a≤3, where ω A is the mass percentage of the glass phase A in the resistor paste, ω B is the mass percentage of the glass phase B in the resistor paste, ω C is the mass percentage of the glass phase C in the resistor paste; Taking the total mass percentage of the glass phase A as 100%, the glass phase A includes the following components in mass percentage: SiO2 32-51%, Al2O3 11-25%, B2O3 12-23%, metal oxide M5-35%, wherein the metal oxide M is selected from at least two of CaO, MgO, SrO, and BaO; Taking the total mass percentage of the glass phase B as 100%, the glass phase B includes the following components in mass percentage: SiO2 30-50%, Al2O3 0-5%, B2O3 5-20%, ZnO 10-20%, metal oxide N 5-25%, metal oxide R 5-25%, wherein the metal oxide N is selected from at least two of SnO2, TeO2, TiO2, and ZrO2; Taking the total mass percentage of the glass phase C as 100%, the glass phase C includes the following components in mass percentage: SiO2 15-30%, Al2O3 0-15%, B2O3 0-25%, metal oxide P 30-55%, metal oxide R 0-20%, wherein the metal oxide P is selected from at least one of CuO, NiO and ZnO; In the glass phase B and the glass phase C, the metal oxide R is each selected from at least one of Li2O, Na2O, and K2O.
2. The resistor paste according to claim 1, characterized in that In the glass phase A, the following relationship is satisfied: b = (ω SiO2 +ω Al2O3 +ω B2O3 ) / ω M , 3≤b≤10, where ω SiO2 is the mass percentage of SiO2 in the glass phase A, ω Al2O3 is the mass percentage of Al2O3 in the glass phase A, ω B2O3 is the mass percentage of B2O3 in the glass phase A, ω M is the mass percentage of the metal oxide M in the glass phase A.
3. The resistor paste according to claim 1, characterized in that In the glass phase B, the following relationship is satisfied: c = (ω SiO2 +ω Al2O3 +ω B2O3 +ω ZnO ) / (ω N +ω BR ), 1.4≤c≤6.8, where ω SiO2 is the mass percentage of SiO2 in the glass phase B, ω Al2O3 is the mass percentage of Al2O3 in the glass phase B, ω B2O3 is the mass percentage of B2O3 in the glass phase B, ω ZnO is the mass percentage of ZnO in the glass phase B, ω N is the mass percentage of the metal oxide N in the glass phase B, ω BR is the mass percentage of the metal oxide R in the glass phase B.
4. The resistor paste according to claim 1, characterized in that In the glass phase C, the following relationship is satisfied: d = (ω SiO2 +ω Al2O3 +ω B2O3 ) / (ω P +ω CR ), 0.68≤d≤1.85, where ω SiO2 is the mass percentage of SiO2 in the glass phase C, ω Al2O3 is the mass percentage of Al2O3 in the glass phase C, ω B2O3 is the mass percentage of B2O3 in the glass phase C, ω P is the mass percentage of the metal oxide P in the glass phase C, ω CR is the mass percentage of the metal oxide R in the glass phase C.
5. The resistor paste according to claim 1, characterized in that: The average particle size of the glass phase is 0.5-5 μm.
6. The resistor paste according to claim 1, characterized in that: The invention also comprises the following components in percentage by mass: 40-85% of conductive phase, 2-10% of resin, 5-20% of organic solvent, 0-10% of inorganic filler and 0-10% of organic additive.
7. The resistor paste according to claim 6, characterized in that: The conductive phase includes copper powder and nickel powder and satisfies the following relationship: s=ω Cu / ω Ni , 0.6≤s≤11, where ω Cu is the mass percentage of the copper powder in the resistor paste, ω Ni is the mass percentage of the nickel powder in the resistor paste.
8. The resistor paste according to claim 6, characterized in that The average particle size of the conductive phase is 0.1-5 μm.
9. The resistor paste according to claim 6, characterized in that: Include at least one of the following: The resin is selected from at least one of ethyl cellulose, epoxy resin, polyurethane resin, polyester resin, acrylic resin, alkyd resin, phenolic resin, petroleum resin, terpene resin, modified rosin, polyethylene, polypropylene, and polyamide; The organic solvent is selected from at least one of diethylene glycol butyl ether, diethylene glycol butyl ether acetate, terpineol, turpentine, isobornyl acetate, benzyl acetate, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, dibutyl phthalate, toluene, xylene, butanone, cyclohexanone, propylene glycol monomethyl ether, dimethyl phthalate, petroleum ether, and mineral oil; The inorganic filler is selected from at least one of aluminum oxide, zirconium oxide, manganese oxide, titanium oxide, silicon oxide, and nickel oxide; The organic additive is selected from at least one of polyethylene wax, polypropylene wax, polyamide wax, hydrogenated castor oil, organic bentonite, fatty acids, aliphatic amides, aliphatic esters, phosphate esters, polyamides, and polyacrylates.
10. A thick film chip resistor, characterized in that: The invention comprises a resistor film layer prepared by sintering the resistor paste according to any one of claims 1 to 9.